Pleiotropic Long-Term Effects of Atorvastatin on Posttraumatic Joint Contracture in a Rat Model - Erik Wegner; Ekaterina Slotina; Tim Mickan; Sebastian Truffel; Charlotte Arand; Daniel Wagner; Ulrike Ritz; Pol M. Rommens; Erol Gercek; Philipp Drees; Andreas Baranowski (Pharmaceutics, 2022)
The antifibrotic effect of atorvastatin has already been demonstrated in several organ systems. In the present study, a rat model was used to investigate the effect of atorvastatin on posttraumatic joint contracture. Forty-eight Sprague Dawley rats were equally randomized into an atorvastatin group and a control group. After initial joint trauma, knee joints were immobilized for intervals of 2 weeks (n = 16) or 4 weeks (n = 16) or immobilized for 4 weeks with subsequent remobilization for another 4 weeks (n = 16). Starting from the day of surgery, animals received either atorvastatin or placebo daily. After euthanasia at week 2, 4 or 8, joint contracture was determined, histological examinations were performed, and gene expression was assessed. The results suggest that the joint contracture was primarily arthrogenic. Atorvastatin failed to significantly affect contracture formation and showed a reduction in myofibroblast numbers to 98 ± 58 (control: 319 ± 113, p < 0.01) and a reduction in joint capsule collagen to 60 ± 8% (control: 73 ± 9%, p < 0.05) at week 2. Gene expression of α-smooth muscle actin (α-SMA), collagen type I, transforming growth factor β1 (TGF-β1) and interleukin-6 (IL-6) was not significantly affected by atorvastatin. Atorvastatin decreases myofibroblast number and collagen deposition but does not result in an improvement in joint mobility.